The living and the dead : a novel - Enriquez, Antonio (Quezon City, Philippines : Giraffe Books, 1994)
Novels provide us with an alternative source of history. They allow us to enter into a particular world and glimpse the worldview of a specific culture and time. The Living and the Dead, narrated from an omnipotent view point, brings the reader to an understanding of the culture of local aristocrats, particularly in the immediate post World War II Philippines.
Keywords: HISTORY